Landscape ratio: identifying the ideal residential open space configuration through landscape ratiometric process - Diaz, Rina Celina O.; Nappy L. Navarra (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Residential landscape design is attributed to the design of yards and garden merely through placement and specification of planting materials and other landscape elements. Residential landscape design is more than just planting; it embodies both form and practical function. This study introduced ratiometric process in a residential landscape design centered on analyzing and determining the ideal configuration and amount in percentage of open spaces in a private residential lot. The result will be identified as the “landscape ratio” which is defined in this study as the quantity and quality of residential open spaces (ROS). The aim of this thesis is to determine the preferences in the configuration of open spaces in a residential lot of middle-income households, the target market of most residential projects. The preferences, through the survey method, outlined the attributes of a quality private open space specifically viewed in four factors: spatial, social, functional and contextual. The study reported that contextual feature is the most considered attribute of middle-income household in residential open spaces. To compare typical residential open space (ROS) configurations, the Spatial Openness Index (SOI) was applied to determine which configuration provides a higher quality residential environment. Based on the results, the ROS configuration that is maximized in the front area of the property was found to have the highest SOI value. The results of the ROS configuration preferences and SOI ranking determine the ideal landscape ratio that improves the quality of life of middle-income households in a residential development and benefit residential developers in creating house and lot package that best suits the target market. The study concluded that the most preferred ROS configuration of middle-income household – ROS all around the house only ranked second in Spatial Openness Index.
Include appendices
Thesis (Master of Tropical Landscape Architecture) -- University of the Philippines Diliman
Keywords: Residential open space; Landscape architecture